Attachment of V. cholerae with plankton biomass in two different ecological zones of Bangladesh - Sultana, Nahid; Alam, Munirul; Sultana, Marzia; Naser, Muhammad Niamul (The Asia Journal of Applied Microbiology, 2023)
Seasonal variation and planktonic abundance has profound effects on the attachment of V. cholerae the devastating agent for causing cholera. As crustacean plankton is the primitive carrier for the cholera bacterium, which stage is the most efficient for the attachment to V. cholerae however is a most curious interrogation to resolve. Here in this experiment, laboratory microcosms were prepared with estuarine Mathbaria water, saline Paikgacca water and fresh water of lake. These three sets were with their twins among which one was with algal supplementation to feed the plankton and another was without any algae. After two months of rearing, it was found that, Mathbaria water and lake water supported the bacterial growth to enhance along with the nauplii production. On the other hand, among the three contaminated water sources (site-2, site-8 and site-11) in Mathbaria nauplii biomass showed highest peak during the infection period (March-May and September-November) in 2013 and 2014. In Chhatak also nauplii biomass showed highest peak at three contaminated ponds (site-1, site-10 and site-12) during the peak season in the studied year. During the current study nitrogen and phosphorus amount was higher in the contaminated ponds of Mathbaria when there was peak season of cholera. So, micronutrients as well as larval stages of crustacean plankton are dominant biological factor for causing cholera in these two regions of Bangladesh. This experiment will play as a role model to observe the intensity of the attachment of V. cholerae to copepods at their different stages as well as the interrelation of micronutrients in coastal region with the availability of cholera during peak season.